1984
DOI: 10.1073/pnas.81.11.3297
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic acid-binding molecules with high affinity and base sequence specificity: intercalating agents covalently linked to oligodeoxynucleotides.

Abstract: Oligodeoxyribonucleotides covalently linked to an intercalating agent via a polymethylene linker were synthesized. Oligothymidylates attached to an acridine dye (Acr) through the 3'-phosphate group [(Tp),(CH2)mAcr] specifically interact with the complementary sequence. The interaction is strongly stabilized by the intercalating agent. By using absorption and fluorescence spectroscopies, it is shown that complex formation between (Tp),(CH2)mAcr and poly(rA) involves the formation of n A-T base pairs, where n is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
1
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(105 citation statements)
references
References 19 publications
8
95
1
1
Order By: Relevance
“…Several technologies have been developed to overcome this problem. The most notable examples are locked nucleic acids [LNA (24,25)] and peptide nucleic acids [PNA (26)], duplex-stabilizing ligands such as minor groove binders [MGBs (22,23)], and intercalators (53,54) and nucleotide analogues. LNA (55,56) and MGBs (57) are usually incorporated into probes since their use in primers can interfere with the function of DNA polymerases.…”
Section: Discussionmentioning
confidence: 99%
“…Several technologies have been developed to overcome this problem. The most notable examples are locked nucleic acids [LNA (24,25)] and peptide nucleic acids [PNA (26)], duplex-stabilizing ligands such as minor groove binders [MGBs (22,23)], and intercalators (53,54) and nucleotide analogues. LNA (55,56) and MGBs (57) are usually incorporated into probes since their use in primers can interfere with the function of DNA polymerases.…”
Section: Discussionmentioning
confidence: 99%
“…A few examples are worth noting: DNA intercalators are small aromatic molecules which generally bind DNA quite nonselectively at almost any sequence. Tethering an intercalator loosely to an oligonucleotide can very significantly increase overall binding affinity, 45 as the affinity of the intercalator is added to that of the DNA. However, the intercalator will bind along with the oligonucleotide whether or not the oligonucleotide is bound at a correct site (and will even bind when the oligonucleotide is not bound at all).…”
Section: When Is Highmentioning
confidence: 99%
“…Another evidence for the formation of an interstrand cross-link is shown on Figure 5, which exhibits large upfield shifts for protons H5' (4 (29)(30)(31)(32). Cross peaks H6(T1)-H3(pso), H4(pso)-H3(pso), H5'(pso)-H6(T2) and H5'(pso)-H4'(pso) are also observed on the DQF-COSY spectrum, showing that cycloaddition have taken place between the 5-6 double bond ofT1 and the 3-4 (pyrone) double bond of psoralen, and between the 5-6 double bond of T2 and the 4'-5' (furan) double bond ofpsoralen.…”
Section: Location Of the Psoralen Derivativementioning
confidence: 99%
“…The binding of an oligonucleotide to its complementary sequence is a highly specific process governed by stacking interactions between base pairs and by hydrogen-bond formation between complementary bases. We have already shown that covalent attachment of an intercalating agent to an oligodeoxynucleotide strongly increases the stability of hybrid formation (4). Substitution of acridine derivatives by other agents such as an orthophenantroline-Cu complex leads to the cleavage of the complementary strand (5).…”
Section: Introductionmentioning
confidence: 99%